(untitled) (Polis (Santiago), 2018)
Faced with a Latin America mobilized, conflicted and crossed by outbreaks of interactoral, civic-contestatary and political violence, and with abuses of governments that result in citizen complaints and new political practices of the people with no rights, a risk scenario is created for this weak democracy. The author thus analyzes democracy not only in regards electoral processes but covering other edges of this phenomenon, such as participation, demonstrations, new actors and behaviors of crowds, seeking to account for the risks of democracy.